Coping Stress of the COVID-19 Pandemic among Medical and Non-Medical Undergraduate Students at Universitas Padjadjaran, Bandung, Indonesia - Wulan Mayasari; Devia Oktaviandra; Fathurachman Fathurachman (Althea Medical Journal, 2021)
Background: Coping stress is an act of dealing with stress by adapting to the problems of the thought process. The ‘Distance Learning’ policy is a stress factor during the COVID-19 pandemic which may have an impact on psychological conditions and coping stress. This study aimed to determine differences in stress levels and coping stress among medical and non-medical undergraduate students against the global COVID-19 pandemic.Methods: Cross-sectional analytical methods were used. Stratified random sampling recruiting undergraduate students, including from medical students (n=80) and non-medical students (n=84) at Universitas Padjadjaran class 2017–2019. The distributed questionnaire contained 25 questions adapted from the Depression Anxiety Stress Scale (DASS 42) and the Cope Inventory. Validity and reliability tests were carried out previously, and statistical analysis was performed using SPSS v.26.Results: The median age of both groups was 21 years and most of the respondents were female. There was no significant difference in stress and coping stress. At the time of coping, the medical students focused more on emotions and the non-medical students focused more on the problems.Conclusion: There is no difference in the levels of stress and coping stress with emotional and problems focus in the medical and non-medical students.